The impact of adopting e-government as a mechanism to enhance accountability as well as transparent conduct within public institutions - Barbra Marufu; Tawanda Manenji (Scholedge Publishing, 2023)
This study examines the impact of adopting e-government as a mechanism to enhance accountability as well as transparent conduct within public institutions in Zimbabwe. There is a belief that e-government brings about better change in governance issues through active disclosure of governance information. The research found out that e-government in Zimbabwe though still being nurtured, has better prospects and there is great need for clearly setting and meeting a conducive environment for it to flourish. That is a set of pre-requirements need to be assessed before trying to implement e-government into full swing. Zimbabwe lacks an unanimous e-government strategy across its ministries hence the existence of disparities in e-government adoption within the country – some ministries are more advanced while others only exhibit the first initial stages of e-government. However, the adoption of e-government in Zimbabwe has been hampered by a plethora of challenges ranging from politics, economics, social and technological. Among them include inadequate or weak legislative frameworks guiding and directing e-government implementation, budget constraints, digital divide as well as technological incompetence. The study also makes some recommendations as to how e-government prospects can be fully attained and such remedies among others include the passing of a comprehensive IT policy which cut across all government ministries, embracing Public Private Partnerships in building IT infrastructure, and redefining government’s top priorities and focus much on e-government investment. The paper also notes the effects of poor governance to a country. Zimbabwe’s e-government strategy if managed properly, would also reduce government external debt, improve service delivery, promote economic development, and increase public accountability and transparency within the public sector.